Individual differences in young offender emotional behaviour - Clarbour, J. (Legal and criminological psychology, 2009)
Purpose. Recent research into adolescent emotional behaviour has confirmed a three-factor structure for emotional style in samples of children and adolescents, ranging in age from nine to nineteen years (Clarbour & Roger, 2004). This study was aimed at replicating the factor structure for the Emotional Behaviour Scale (EBS) amongst young offenders, and investigating the role of the factors in offender behaviour. Method. Both exploratory and confirmatory factor analyses were used to compare the responses of 307 male young offenders to those of 294 schoolchildren. A subsample of 264 offenders additionally completed indices of offending behaviour that were used for further validation of the EBS amongst young offenders. Results and conclusions. The three emotional style factors obtained for schoolchildren - social anxiety, malevolent aggression and social self-esteem - were confirmed in the young offender sample. Lower scores on malevolent aggression, and higher scores on social anxiety and social self-esteem, were significantly associated with later first police contact. High malevolent aggression and lower social anxiety were also significantly associated with placement on Governor's report, and high malevolent aggression was associated with violent offence types. The three scales were also found to relate systematically and predictably to a range of other personality and emotional style scales.